Adaptative Up-Regulation of PRX2 and PRX5 Expression Characterizes Brain from a Mouse Model of Chorea-Acanthocytosis - Enrica Federti; Alessandro Matte; Veronica Riccardi; Kevin Peikert; Seth L. Alper; Adrian Danek; Ruth H. Walker; Angela Siciliano; Iana Iatcenko; Andreas Hermann; Lucia De Franceschi (Antioxidants, 2021)
The peroxiredoxins (PRXs) constitute a ubiquitous antioxidant. Growing evidence in neurodegenerative disorders such as Parkinson’s disease (PD) or Alzheimer’s disease (AD) has highlighted a crucial role for PRXs against neuro-oxidation. Chorea-acanthocytosis/Vps13A disease (ChAc) is a devastating, life-shortening disorder characterized by acanthocytosis, neurodegeneration and abnormal proteostasis. We recently developed a Vps13a−/− ChAc-mouse model, showing acanthocytosis, neurodegeneration and neuroinflammation which could be restored by LYN inactivation. Here, we show in our Vps13a−/− mice protein oxidation, NRF2 activation and upregulation of downstream cytoprotective systems NQO1, SRXN1 and TRXR in basal ganglia. This was associated with upregulation of PRX2/5 expression compared to wild-type mice. PRX2 expression was age-dependent in both mouse strains, whereas only Vps13a−/− PRX5 expression was increased independent of age. LYN deficiency or nilotinib-mediated LYN inhibition improved autophagy in Vps13a−/− mice. In Vps13a−/−; Lyn−/− basal ganglia, absence of LYN resulted in reduced NRF2 activation and down-regulated expression of PRX2/5, SRXN1 and TRXR. Nilotinib treatment of Vps13a−/− mice reduced basal ganglia oxidation, and plasma PRX5 levels, suggesting plasma PRX5 as a possible ChAc biomarker. Our data support initiation of therapeutic Lyn inhibition as promptly as possible after ChAc diagnosis to minimize development of irreversible neuronal damage during otherwise inevitable ChAc progression.